G297(P) The utility of ketones at triage. (24th May 2017) - Durnin, S; Blackburn, C; Ryan, E; Dobos, E; Conway, B; O'Donnell, SM; Walsh, S; Barrett, MJ
Abstract : Aims: The role of point-of-care (POC) ketones in relation to acute dehydration with ketosis in the paediatric emergency department (PED) has yet to be established. Previous studies highlight that clinical symptoms and tests are inexact in discerning the degree of dehydration and predicting the clinical course in the PED. The aim of this study was to establish the relationship between triage POC ketones with clinical dehydration as per the validated Gorelick Score in the PED. Secondary outcomes were the relationship between patient disposition with initial ketone levels and the rate of change of ketones in response to treatment. Methods: A prospective cohort study commenced in April 2016 recruiting patients, less than 5 years old, with vomiting and/or diarrhoea or decreased intake with signs of dehydration or clinician concern for hypoglycaemia. Ethics approval was attained. POC ketones were analysed at triage and at 4 hours later or on discharge if sooner. The study's target is to recruit 200 patients. Results: To date, there have been 161 recruitments; median age of 1.84 years (range 2 months to 4.99 years); 84 (53.2%) male. Median (interquartile range(IQR)) modified Gorelick dehydration score of 2 (IQR 2–3) consistent with moderate dehydration. The median triage ketones were 4.3 (IQR 2.8–5.6) mmol/L and the median triage glucose was 3.5 (range 1.7–7.9) mmol/L. No correlation between triage ketones and clinical dehydration score existed (Pearson's r=0.134, p=0.091). Forty-eight (29.8%) patients were admitted. Those admitted to hospital had median triage ketone of 5.1 (IQR 4–6.1) mmol/L compared with 4.2 (IQR 2.4–5.2) mmol/L in those discharged home (p=0.02). The median ketones after treatment was 4.9 (IQR 3.5–5.8) mmol/L among patients admitted compared with 2.9 (IQR 1.4–4.2) mmol/L those who were discharged (p=0.002). There was a mean reduction of 0.76 (range +2.3 to 6.2)mmol/L in ketones after rehydration. Patients discharged had tendency toward greater reduction than admitted patients ( 0.9 vs. 0.3mmol/L, p=0.13). Conclusion: Interim results have revealed no correlation between ketones at triage and level of clinical dehydration. A significant relationship was established between initial ketones and admitted patients. This study provides further evidence of the potential utility of ketones in the acute management of children with dehydration.